USTP- Panaon Recompense Waste Management: Automated Segregation and Web-Based Notifications - Hilot, Crichpe A; Beniga, Janjel S; Maca-ambac, Sheena L; Pizana, Marchel P; Amin, Warnner Daminar (Universitas Multi Data Palembang, 2025)
Recompense Waste Management: Automated Waste Segregation and Web-Based Notifications provides a novel solution to the growing problem in the field of waste management. The system aimed to enhance the segregation and disposal of waste provides automation and a technological approach to it making it efficient, sustainable, and accountable. Functionality The main function is automatically sorting waste, identifying biodegradable and non-biodegradable waste, rejecting expired waste. Smart segregation can be simplified by using smart segregation bins with advanced sensor technology.